2022
DOI: 10.3389/fsurg.2022.811005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Choledochoduodenostomy and Hepaticogastrostomy for EUS-Guided Biliary Drainage: A Meta-Analysis

Abstract: BackgroundAlthough endoscopic ultrasound-guided choledochoduodenostomy (EUS-CDS) or hepaticogastrostomy (EUS-HGS) has emerged as an option for patients of failed endoscopic retrograde cholangiopancreatography (ERCP), there has no agreement on which approach is preferred. Therefore, a meta-analysis was performed to examine the two methods.MethodsWe performed a comprehensive search in databases of PubMed, Embase, and Cochrane library to find relevant studies reporting the efficacy and safety of the two EUS-guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…In our cohort, modifying stent position using accessories like snare in case of mal-deployed stent or deploying another SEMS inside the migrating one (Tandem stent placement (34)) were beneficial options. In the same to previous studies, with overall risk in the literature for HGS as 19% (ranging from 0-35%) ( 27) and 13.6-20% in CDS (26). Most AE occurred in our study were mild (8.2), but unfortunately one fatal outcome was met in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our cohort, modifying stent position using accessories like snare in case of mal-deployed stent or deploying another SEMS inside the migrating one (Tandem stent placement (34)) were beneficial options. In the same to previous studies, with overall risk in the literature for HGS as 19% (ranging from 0-35%) ( 27) and 13.6-20% in CDS (26). Most AE occurred in our study were mild (8.2), but unfortunately one fatal outcome was met in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Considerably, in such a developing country in the Middle East with a relatively low income, this advanced Nonetheless, the median duration of CDS was 2 minutes less than HGS. A more recent meta-analysis by Li et al, (26) has supported that CDS was slightly faster and they recommended to limit the number of accessory changes during HGS to decrease the process duration.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with EUS-HGS, the pooled OR of EUS-CDS was 0.74 (95% CI, 0.33-1.65; P = 0.46) for technical success and 0.94 (95% CI, 0.56-1.59; P = 0.83) for clinical success. 25 EUS-CDS was associated with a moderately shorter procedure time (-2.68 min) and significantly fewer early adverse events than EUS-HGS (12.2% vs 17.5%; OR, 0.58; P = 0.02).…”
Section: Eus-guided Hepaticogastrostomymentioning
confidence: 87%
“…In another meta-analysis of 12 studies with 623 patients (EUS-CDS: 303 and EUS-HGS: 320), the cumulative technical success and clinical success for EUS-CDS and EUS-HGS was 95.0 and 93.1% and 96.6 and 91.3%, respectively. 27 The cumulative early adverse events for EUS-CDS and EUS-HGS was 12.2 and 17.5%, respectively.…”
Section: Recommendation 12mentioning
confidence: 93%
“…25 In a study in patients with combined duodenal and distal biliary obstruction where both EUS-CDS and EUS-HGS can be used, it was shown that EUS-HGS has a significant risk of adverse events and it was proposed that, EUS-CDS may be the first choice in this subset of patients. 26 Li et al 27 compared EUS-HGS and EUS-CDS in a meta-analysis of 12 studies including 2 randomized controlled trials (RCTs) and showed that the cumulative technical success and clinical success for EUS-CDS and EUS-HGS was 95.0% (288/303) and 93.1% (268/288), and 96.6% (309/320) and 91.3% (282/309), respectively. Compared with EUS-HGS, the pooled odds ratio (OR) was 0.74 (95% confidence interval [CI] 0.33–1.65; p = 0.46) for EUS-CDS technical success and 0.94 (95% CI 0.56–1.59; p = 0.83) for clinical success suggesting no significant difference between CDS and HGS.…”
Section: Methodsmentioning
confidence: 99%